AN EXTENSION OF THE FAILURE MODE EFFECTS AND CRITICALITY ANALYSIS WITH FUZZY ANALYTICAL HIERARCHY PROCESS METHOD TO ASSESS THE EMERGENCY SAFETY BARRIERS - Samia, Daas; Innal, Fares (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The emergency safety barrier is one of the reactive technical safety barriers in industrial facilities. Degrade of emergency safety barriers can lead to a major accident with serious consequences for people, property and the environment. In this context, the purpose of this article is to present a proposed methodology to identify these deficiencies, thus ensuring the effectiveness of the emergency safety barriers. This paper presents an integrated approach that uses fuzzy set theory, extension of failure modes, effects and criticality analysis and the fuzzy analytic hierarchy process method to deal with uncertainty in decision-making related to the prioritization of risk factors. These risk factors are the prioritization of corrective actions associated with the most critical disturbance modes to improve the reliability of emergency safety barriers. In addition, a Liquefied Petroleum Gas production facility was selected as a case study to assess the emergency safety barriers. The results show that the proposed methodology provides the possibility to evaluate the fire-fighting systems. In addition, the fuzzy analytical approach method is the most reliable and accurate. Therefore, some corrective actions are suggested to reduce the failure criticality of the emergency safety barriers and help practitioners prioritize the improvement of the emergency safety barriers of the Liquefied Petroleum Gas storage facility. This paper has an important role in the dysfunctional analysis of the emergency safety barriers related to the others effects of the release of LPG, such as the effects of domino scenarios.